Asian video cultures in the penumbra of the global - Neves, Joshua; Sarkar, Bhaskar (Durham Duke University Press Books, 2017)
The contributors to this volume theorize Asian video cultures in the context of social movements, market economies, and local popular cultures to complicate notions of the Asian experience of global media. Whether discussing video platforms in Japan and Indonesia, K-pop reception videos, amateur music videos circulated via microSD cards in India, or the censorship of Bollywood films in Nigeria, the essays trace the myriad ways Asian video reshapes media politics and aesthetic practices.

While many influential commentators overlook, denounce, and trivialize Asian video, the contributors here show how it belongs to the shifting core of contemporary global media, thereby moving conversations about Asian media beyond static east-west imaginaries, residual cold war mentalities, triumphalist declarations about resurgent Asias, and budding jingoisms.

In so doing, they write Asia's vibrant media practices into the mainstream of global media and cultural theories while challenging and complicating hegemonic ideas about the global as well as digital media.
Keywords: Mass media -- Political aspects -- Asia; Mass media -- Social aspects -- Asia; Digital media -- Social aspects -- Asia; Video recording -- Social aspects -- Asia